The vascular endothelial growth factor (VEGF) receptor-2 is a major regulator of VEGF-mediated salvage effect in murine acute hepatic failure - Namisaki, Tadashi; Yoshiji, Hitoshi; Noguchi, Ryuichi; Ikenaka, Yasuhide; Kitade, Mitsuteru; Kaji, Kosuke; Shirai, Yusaku; Aihara, Yosuke; Yoshii, Junichi; Yanase, Koji; Tsujimoto, Tatsuhiro; Kawaratani, Hideto; et al. (Vascular Cell, 2010)
Abstract   Although administration of the vascular endothelial growth factor (VEGF), a potent angiogenic factor, could improve the overall survival of destroyed sinusoidal endothelial cells (SEC) in chemically induced murine acute hepatic failure (AHF), the mechanistic roles of the VEGF receptors have not been elucidated yet. The respective roles of VEGF receptors; namely, Flt-1 (VEGFR-1: R1) and KDR/Flk-1 (VEGFR-2: R2), in the D-galactosamine (Gal-N) and lipopolysaccharide (LPS)-induced AHF were elucidated with specific neutralizing monoclonal antibody against R1 and R2 (R1-mAb and R2-mAb, respectively). The serum ALT elevation, with a peak at 24 h after Gal-N+LPS intoxication, was markedly augmented by means of the R1-mAb and R2-mAb. The aggregative effect of R2-mAb was more potent than that of R1-mAb, and the survival rate was 70% in the R2-mAb-treated group and 100% in the other groups. The results of SEC destruction were almost parallel to those of the ALT changes. Our in-vitro study showed that R1-mAb and R2-mAb significantly worsened the Gal-N+LPS-induced cytotoxicity and apoptosis of SEC mediated by caspase-3, which were almost of similar magnitude to those in the in-vivo study. In conclusion, these results indicated that R2 is a major regulator of the salvage effect of VEGF on the maintenance of SEC architecture and the anti-apoptotic effects against chemically-induced murine AHF.